2005
DOI: 10.1097/01.blo.0000180451.03425.48
|View full text |Cite
|
Sign up to set email alerts
|

Shock Wave Therapy for Chronic Achilles Tendon Pain

Abstract: Therapeutic study, Level I (systematic review of Level I RCTs-and study results were homogenous). See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0
13

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 19 publications
1
101
0
13
Order By: Relevance
“…In the series from the UK, 16 affected tendons in 15 patients improved-as measured by the AOFAS score and the Visa A score systems (Lakshmanan et al 2004). The randomized study (Costa et al 2005), which was published while we were conducting our study, indicated no effect of ESWT. In that study, the treatment group was 10 years younger on average than the placebo group.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the series from the UK, 16 affected tendons in 15 patients improved-as measured by the AOFAS score and the Visa A score systems (Lakshmanan et al 2004). The randomized study (Costa et al 2005), which was published while we were conducting our study, indicated no effect of ESWT. In that study, the treatment group was 10 years younger on average than the placebo group.…”
Section: Discussionmentioning
confidence: 98%
“…Randomized studies on the effect of ESWT in the treatment of plantar heel pain (Krischek et al 1998, Hammer et al 2002 and calcifying shoulder tendonitis (Rompe et al 1997, Loew et al 1999, Haake et al 2001a, Gross et al 2002, Gerdesmeyer et al 2003, Pleiner et al 2004 have also yielded conflicting results. One randomized study (Costa et al 2005), 2 uncontrolled studies (Perlick et al 2002, Lakshmanan et al 2004, and 1 controlled (Furia 2005) trial included ESWT in the treatment of Achilles tendinopathy. In the series from Germany, 29 of 40 patients showed satisfactory results (Perlick et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to recent randomized control studies on chronic Achilles tendinopathy, repeated shock wave treatments with weekly interval has shown to be effective in a carefully selected group of patients, 30,31 while monthly exposure of shock wave did not show any significant effect. 32 It is also reported that repeated application of shock wave had a cumulative effect on decreasing epidermal free nerve endings in rats. 33 The importance of the frequency of the treatment suggests that the chronic inflammatory condition in Achilles tendon could be easy to recur after the isolated shock wave treatment.…”
Section: Cell) (B)mentioning
confidence: 99%
“…Costa et al [13] reported no statistically significant treatment effects in 49 patients with Achilles tendinopathy treated with low-energy SWT. Patients with insertional and noninsertional forms of Achilles tendinopathy were included in the trial.…”
Section: Extracorporeal Shock Wave Therapymentioning
confidence: 99%